Development, implementation, and characterization of a standalone embedded viscosity measurement system based on the impedance spectroscopy of a vibrating wire sensor - Santos, José (2016)
This paper presents an embedded liquid viscosity measurement system based on a vibrating wire sensor. Although multiple viscometers based on different working principles are commercially available, there is still a market demand for a dedicated measurement system capable of performing accurate, fast measurements and requiring little or no operator training for simple systems and solution monitoring. The developed embedded system is based on a vibrating wire sensor that works by measuring the impedance response of the sensor, which depends on the viscosity and density of the liquid in which the sensor is immersed. The core of the embedded system is a digital signal processor (DSP) which controls the waveform generation and acquisitions for the measurement of the impedance frequency response. The DSP also processes the acquired waveforms and estimates the liquid viscosity. The user can interact with the measurement system through a keypad and an LCD or through a computer with a USB connection for data logging and processing. The presented system is tested on a set of viscosity standards and the estimated values are compared with the standard manufacturer specified viscosity values. A stability study of the measurement system is also performed.